Enhanced overall and progression-free survival in advanced melanoma patients undergoing targeted therapy alongside antithrombotic treatment: insights from a multicenter study involving 1296 patients from the prospective skin cancer registry ADOReg - Zimmermann, Noah; Kött, Julian; Zell, Tim; Abedini, Ali Zeinal; Blomen, Chiara L.; Belz, Stella; Deitert, Benjamin; Heidrich, Isabel; Geidel, Glenn; Rünger, Alessandra; Smit, Daniel J.; Weichenthal, Michael; et al. (European journal of cancer, 2026)
Background - Targeted therapies (TT) improve outcomes in BRAF-mutant melanoma. Pre-clinical data suggest that anticoagulation (AC) and platelet aggregation inhibition (PAI) may have antitumoral effects. We evaluated the impact of concomitant AC or PAI on outcomes in patients receiving TT. - Methods - We analyzed 1296 patients with unresectable stage III-IV BRAF-mutant melanoma treated with BRAF plus MEK inhibitors (2016-2024) in the prospective multicenter ADOReg registry. Patients were categorized as receiving no antithrombotic therapy (ATT; n=1125), PAI (n=73; acetylsalicylic acid or clopidogrel), or AC (n=98; direct oral anticoagulants, low-molecular-weight heparin, or vitamin K antagonists). - Results - Median follow-up was 1.3 years. Compared with patients without ATT, those receiving AC had significantly improved 12-month progression-free survival (PFS; HR 0.55, 95 % CI 0.39-0.78, p=0.001) and overall survival (OS; HR 0.35, 95 % CI 0.19-0.64, p=0.001). Direct oral anticoagulants showed the most pronounced PFS benefit (HR 0.40, 95 % CI 0.25-0.64, p<0.001). PAI was not associated with a significant difference in PFS, but multivariable Cox regression indicated a reduced hazard of death (HR 0.48, 95 % CI 0.27-0.87, p=0.015). - Conclusion - Concomitant AC, particularly factor Xa-inhibiting direct oral anticoagulants, was associated with improved survival in melanoma patients undergoing TT. These findings support prospective trials evaluating AC as concomitant therapy in advanced melanoma.
Online verfügbar: 19. Dezember 2025, Artikelversion: 24. Dezember 2025
Gesehen am 23.02.2026